2007
DOI: 10.1161/01.str.0000251805.47370.91
|View full text |Cite
|
Sign up to set email alerts
|

The Socioeconomic Gradient in the Incidence of Stroke

Abstract: Background and Purpose-A socioeconomic gradient in stroke has been demonstrated in a variety of settings, but mostly in men. Our purpose was to establish whether a socioeconomic gradient in stroke existed in a group of Swedish women and whether this gradient could be explained by established stroke risk factors or psychosocial factors. Methods-The Women's Lifestyle and Health Cohort Study includes 49 259 women from Sweden aged 30 to 50 years at baseline (1991 to 1992). The women completed an extensive question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
3
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(79 citation statements)
references
References 23 publications
5
69
3
1
Order By: Relevance
“…participants identified a strong relationship between the incidence of stroke and years of schooling, showing that the incidence was two times higher among people with a low education (22) .…”
Section: Discussionmentioning
confidence: 99%
“…participants identified a strong relationship between the incidence of stroke and years of schooling, showing that the incidence was two times higher among people with a low education (22) .…”
Section: Discussionmentioning
confidence: 99%
“…This is somewhat in line with previous studies. Regarding high strain, two longitudinal studies have shown non-significant results with mostly marginally increased risk estimates (13,18), and in another two studies there was moderately, still non-significant, increased risk (14,19). In a Japanese study there are quite high risk estimates for most dimensions of the JDC model, although only significant for high strain in all types of stroke (21).…”
Section: Discussionmentioning
confidence: 90%
“…All items were scored using a scale (1-5) ranging from "seldom" to "often". Job control consisted of three items (range 3-15), job demand of four items (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and social support of two items (range 2-10). In order to reduce the amount of missing data, control and demand were imputed using the mean of the remaining values for subjects with only one missing item.…”
Section: Psychosocial Variablesmentioning
confidence: 99%
See 2 more Smart Citations